Differential expression of cytokines in PBMC of Bos indicus and Bos taurus × Bos indicus cattle due to Brucella abortus S19 antigen. Issue 2 (3rd March 2020) - Kumar, D. Ravi; Sivalingam, Jayakumar; Mishra, Shailendra K.; Kumar, Anshuman; Vineeth, M. R.; Chaudhuri, Pallab; Kataria, R. S.; Niranjan, S. K.
Abstract: Brucellosis is the most dreadful disease among bovines, although breed differences have been observed in prevalence of disease, worldwide. In present study, antibody response and relative expression of proinflammatory cytokines was compared in Bos indicus (zebu) and Bos taurus × Bos indicus (crossbred) cattle vaccinated by live attenuated Brucella abortus S19 antigen. Six female calves (4–6 months age) of both groups were vaccinated with B.abortus S19 strain. Blood samples were collected before vaccination (0d) and 7 th (7d), 14 th (14d) and 28 th (28d) days after vaccination. Indirect ELISA showed high ( p  < .05) anti- Brucella antibody level after vaccination; with no significant difference between the groups. During Real-time expression, IFNγ, TNFα, IL6 and IL10 genes initially showed down regulation followed by upregulation in both the groups; however, the trend was much prominent in crossbreds. The expressions of IFNγ, TNFα and IL6, proinflammatory molecules important for initial containment of the Brucella were significantly ( p  < .01) higher in crossbred. The study showed that the Sahiwal cattle were less responsive to B.abortus S19 antigen than crossbreds, indicating its lower sensitivity to the Brucella, comparatively. In contrary, higher expression of the proinflammatory molecules in crossbreds could be important for containment of the organism during initial stage of infection.